The Stability of Self-Concept between Elementary and Junior High School in Catholic School Children - Scott, Amy; Santos de Barona, Maryann (Catholic Education: A Journal of Inquiry and Practice, 2011)
Researchers have found that self-concept in students fluctuates during times of change, such as the physical transition between elementary school and junior high. Since Catholic school students typically do not have the physical transition or social network changes in junior high, it was hypothesized that their self-concepts would not fluctuate. One hundred ninety-five ethnically diverse Catholic school students rated how they think and feel about their general, self-image, academic, and social self-concepts, as well as how important each item was to their self-concept. Students were initially in fourth, fifth, and sixth grade and subsequently in sixth, seventh, and eighth grade at the time of the longitudinal study. Overall, the results indicated that ratings of self-concept and the importance of the items remained stable between elementary and junior high school and for students of varying ethnicities. The results are compared to the findings from other studies. The lack of a physical transition and social network changes from elementary school to junior high may assist students from developing significantly lower self-concept in junior high, especially in academic and social self-concept.